Health Beneficial Effects of Moomiaii in Traditional Medicine: - Rahmani Barouji, Solmaz; Fazljou, Seyyed Mohammad Bagher; Yari Khosroushahi, Ahmad; Torbati, Mohammadali; Saber, Amir (Galen Medical Journal, 2020)
raditional medicine (TM) that developed over the years within various societies consists of medical experimental knowledge and practices, which apply natural methods and compounds for general wellness and healing. Moomiaii as a pale-brown to blackish-brown natural exudate is one of the natural compounds in traditional medicine that has been used over 3000 years in many countries of the world especially in India, China, Russia, Iran, Mongolia, Kazakhstan and Kirgizstan. We reviewed all English-language studies about Moomiaii that we accessed them. In traditional medicine, many beneficial activities have been attributed to Moomiaii and to its main constituents, Humic acid and Fulvic acid, which are widely used to prevent and treatment of different diseases. Some modern scientific investigations showed that Moomiaii as a safe dietary supplement can be beneficial in various health complications. Even though the beneficial effects of Moomiaii have been confirmed in traditional and modern medicine, it seems that additional in-vitro/in-vivo studies and comprehensive clinical trials are necessary to explain the whole mechanisms of action and to determine the effective doses in various diseases. We discuss and clarify the claimed health beneficial effects of Moomiaii in some wide-spread diseases regarding its anti-ulcerogenic, immunomodulatory, antidiabetic, antioxidative and anticancer properties. [GMJ.2020;9:e1743]